Phase II study of patients with peritoneal carcinomatosis from gastric cancer treated with preoperative systemic chemotherapy followed by peritonectomy and intraperitoneal chemotherapy. (May 2013) - Hultman, Bo; Lind, Pehr; Glimelius, Bengt; Sundbom, Magnus; Nygren, Peter; Haglund, Ulf; Mahteme, Haile
Abstract Background. The aim was to evaluate the feasibility and the effectiveness of neoadjuvant systemic chemotherapy followed by cytoreductive surgery (CRS), hyperthermic intraperitoneal chemotherapy (HIPEC) and early postoperative intraperitoneal chemotherapy (EPIC) in patients with peritoneal carcinomatosis (PC) from gastric cancer. Material and methods. Eighteen patients (median age 57 years, range 38–74) were scheduled for three months' neoadjuvant systemic chemotherapy followed by CRS + HIPEC + EPIC. Results. At the time of surgery, the peritoneal tumor burden was extensive with tumor growth on the entire peritoneal cavity. Only eight patients received the entire treatment and OS was 14.3 months (range 6.1–34.3, 95% CI 6.6–20.3). Six patients had macroscopically radical (CC0) surgery and for this subgroup OS was 19.1 months (range 6.1–34.3, 95% CI 6.9–27.1). Postoperative 90-day mortality was 10% (one patient) and the perioperative grades II–IV adverse events (AE) rate was 62.5%. Discussion. Neoadjuvant chemotherapy followed by CRS + HIPEC + EPIC does not seem to be associated with prolonged OS in patients with extensive PC growth from gastric cancer unless macroscopically radical surgery is achieved. However, morbidity from this treatment is considerable and it cannot be recommended for routine care until a prospective randomized trial has been performed.